Singularity of fifth grade pupils anxiety - Vinarchik, Elena; Balashova, Svetlana (Видавництво Львівської політехніки, 2013)
Features of the correction program sent to the decline of level of anxiety of fifth grade pupils by the methods of musical therapy.
Keywords: therapy; anxiety; pupils; correction program; psychotherapy